2017
DOI: 10.28920/dhm47.4.223-227
|View full text |Cite
|
Sign up to set email alerts
|

Influence of repetitive diving in freshwater on pressure equalization and Eustachian tube function in recreational scuba divers

Abstract: Introduction: We investigated the effect of repetitive pressure exposure during freshwater dives on Eustachian tube function and the middle ear, assessed by the Eustachian tube function test (ETFT). Methods: This prospective observational cohort study included 23 divers over three consecutive days of diving in freshwater lakes in Nordhausen, Germany. Participants underwent otoscopy and ETFT before the first dive, between each dive and after the last dive. ETFT included regular tympanometry (R-tymp), tympanomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…This symptom mainly aff ected people with allergic rhinitis or acute rhinitis [15]. In contrast, Jansen et al showed signifi cantly higher middle ear peak pressures and higher pressure diff erences after equilibration maneuvers in people with exposure of the Eustachian tube to increased atmospheric pressure [6,13]. Therefore, any patient who reports the symptom of a "plugged ear" should have a tympanometry test.…”
Section: Discussionmentioning
confidence: 99%
“…This symptom mainly aff ected people with allergic rhinitis or acute rhinitis [15]. In contrast, Jansen et al showed signifi cantly higher middle ear peak pressures and higher pressure diff erences after equilibration maneuvers in people with exposure of the Eustachian tube to increased atmospheric pressure [6,13]. Therefore, any patient who reports the symptom of a "plugged ear" should have a tympanometry test.…”
Section: Discussionmentioning
confidence: 99%